2023
DOI: 10.1007/s12185-023-03589-9
|View full text |Cite
|
Sign up to set email alerts
|

Severe systemic inflammation mimicking TAFRO syndrome following COVID-19

Abstract: TAFRO syndrome is a rare systemic inflammatory disease. Its pathogenesis mainly involves excessive cytokine secretion and autoimmune dysfunction. Although its etiology is unclear, some viral infections have been reported to cause it. Here, we report a case of severe systemic inflammation mimicking TAFRO syndrome that arose after COVID-19. A 61-years-old woman suffered from a continuous fever, ascites, and edema after contracting COVID-19. She developed progressive thrombocytopenia, renal failure, and elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In severe cases of COVID-19, the level of IFN-I has been increased over time 43 . A Case that presented with TAFRO-like symptoms after the onset of COVID-19 was positive for anti-SS-A antibody 44 . Based on the above, it is possible that the IFN-I response triggered by such as viral infection may be involved in the development of both anti-SS-A antibodies and TAFRO-like manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…In severe cases of COVID-19, the level of IFN-I has been increased over time 43 . A Case that presented with TAFRO-like symptoms after the onset of COVID-19 was positive for anti-SS-A antibody 44 . Based on the above, it is possible that the IFN-I response triggered by such as viral infection may be involved in the development of both anti-SS-A antibodies and TAFRO-like manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of kidney injury, such as IgA nephropathy [7], minimal change disease [8][9][10], and IgG4-related disease [11], following mRNA vaccination has accumulated in current research. Recently, few cases of TAFRO syndrome [12,13] and iMCD [14] developed after COVID-19 vaccination or COVID-19 infection was reported. Yamada et al reported TAFRO syndrome with a serious clinical course triggered by the second COVID-19 mRNA vaccination [12].…”
Section: Discussionmentioning
confidence: 99%
“…In these two cases, in situ hybridization of lymph node biopsy samples showed cells that were positive for EBV-encoded RNA. Recently, we reported a case of severe systemic inflammation mimicking TAFRO that arose after COVID-19, as described in detail in Section 5 [ 22 ].…”
Section: Etiologies Of Tafro Syndrome and MCD Focusing On Viral Infec...mentioning
confidence: 99%
“…TAFRO syndrome and excessive immunoreaction after severe COVID-19 can induce similar symptoms and pathophysiologies through cytokine storms. A 61-year-old Japanese female was initially reported to have severe systemic inflammation mimicking TAFRO syndrome following COVID-19 [ 22 ]. She developed a fever, anasarca, renal failure, organomegaly, and thrombocytopenia three weeks after COVID-19.…”
Section: Tafro Syndrome and Covid-19mentioning
confidence: 99%